Hubungan Terpaan Kampanye Pemilahan Sampah Dan Intensitas Interaksi Peer Group Dengan Perilaku Pemilahan Sampah Rumah Tangga Oleh Followers @Pilahsampah - Hamidah, Nadiya; Pradekso, Tandiyo; Setyabudi, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Instagram account @pilahsampah has actively promoted a campaign promoting waste sorting behavior, it appears that the practical adoption of this practice has not yet attained an optimal level among @pilahsampah followers. Despite the campaign being conveyed through social media with the intention of providing guidance and encouragement to followers to participate in the responsibility of waste sorting, there exists a gap between the campaign message and the level of waste sorting implementation in household daily life. This research aims to investigate the correlation between the exposure to waste sorting campaigns and the intensity of peer group interaction with household waste sorting behavior among the followers of @pilahsampah. This research employs a quantitative method with an explanatory type, based on the concept of Social Learning Theory. The sampling technique involves non-probability sampling, with a total of 100 respondents who have read, seen, or heard waste sorting campaign messages and are followers of the social media account @Pilahsampah, as well as being part of the Waste Sorting Community. Based on the results of this study using Kendall's W analysis, indicate that there is a relationship between the exposure to waste sorting campaign messages and the intensity of peer group interaction with household waste sorting behavior among followers of @pilahsampah, with a significance value of 0.002. This value is smaller than 0.05, indicating significance.